TRANSITION TO COGNITIVISM MODERN - santi, santi hardiani; Herdiana, Dodi (Journal of Education, 2024)
ABSTRACT In the early 20th century, Cognitive Psychology developed as a reaction to the behavioral approaches prevailing at the time. Behaviorism views human behavior as the result of stimulus and response, without paying attention to the role of thinking. The transition from behaviorism to cognitivism is a change in the understanding of how humans learn and understand the world around them, this involves a shift from an approach that only considers behavior that can be observed externally (Behaviorism) is an approach that recognizes the important role of individual thinking, interpretation and understanding in the formation of knowledge (cognitivism). Important figures in the modern cognitive transition include Hebb, Tolman and the Gestalists. These three figures have different views of thinking, but have similarities in their rejection of the behavioral approach. The aim of this research is to discuss the views of Robert Hebbs, Tolman, and the Gestalists. This influences the modern cognitive transition. This research uses library research methods. Research information was obtained from books, articles, journals and other relevant sources. This research shows that the views of Hebb, Tolman, and Gestalist greatly influenced the development of cognitive psychology. This view helps explain complex human behavior such as thinking, solving problems, learning and expanding understanding of how humans learn and understand the world. Hebb, Tolman, and Gestalis emphasize the importance of individual thinking, understanding and understanding in the process of forming knowledge which is the basis of the Cognitivism approach. . Keywords: Cognitive transition, Hebb's theory, Tolman's theory, Gestalt theory, cognitive processes ABSTRAK Pada awal abad ke-20, Psikologi Kognitif berkembang sebagai reaksi terhadap pendekatan perilaku yang berlaku pada saat itu. Behaviorisme memandang tingkah laku manusia sebagai hasil stimulus dan respon, tanpa memperhatikan peran berpikir. Transisi dari behaviorisme ke kognitivisme merupakan perubahan dalam pemahaman tentang bagaimana manusia belajar dan memahami dunia di sekitarnya,ini melibatkan pergeseran dari pendekatan yang hanya mempertimbangkan perilaku yang dapat di amati secara eksternal (Behaviorisme) menjadi pendekatan yang mengakui peran penting pemikiran,interpretasi,dan pengertian individu dalam pembentukan pengetahuan (kognitivisme).Tokoh penting dalam transisi kognitif modern antara lain Robert Hebb, Tolman,dan Gestalist. Ketiga tokoh ini mempunyai pandangan berpikir yang berbeda, namun memiliki kesamaan dalam penolakannya terhadap pendekatan behavioral.Tujuan dari penelitian ini adalah untuk membahas bagaimana pandangan Robert Hebbs,.Tolman, dan Gestalist. tersebut mempengaruhi transisi kognitif modern.Penelitian ini menggunakan metode penelitian kepustakaan. Informasi penelitian diperoleh dari buku, artikel, jurnal dan sumber lain yang relevan.Penelitian ini menunjukkan bahwa pandangan Hebb, Tolman, dan Gestalist.sangat mempengaruhi perkembangan psikologi kognitif. Pandangan ini membantu menjelaskan perilaku manusia yang kompleks seperti berpikir, memecahkan masalah, dan belajar dan memperluas pehaman tentang bagaimana manusia belajar dan memahami dunia, Hebb,Tolman,dan Gestalis menekankan pentingnya pemikiran,pemahaman dan pengertian individu dalam proses pembentukan pengetahuan yang menjadi dasar dari pendekatan Kognitivisme. kata kunci : Transisi kognitif, Teori Hebb, Teori Tolman, Teori Gestalt, Proses Kognitif